A Quantitative Correlation between Emotional Intelligence and Employee Job Performance: A Study at a Multinational Company in Zambia - Miya Nakazwe (An Overview on Business, Management and Economics Research Vol. 2, 2023)
This study investigates whether Goleman’s four-domain model of emotional intelligence can accurately forecast work success in a multinational corporation in Zambia. Goleman’s four domains of emotional intelligence and their impact on workers’ job performance were examined using a quantitative correlation research study. By using a survey instrument, the study first determined how much an employee recognizes their emotional intelligence skills. A total 164 subordinates were subjected to complete the questionnaire on Subordinate Emotional Intelligence Evaluation (SEIE). A total of 109 questionnaires among 255 employees (subordinate) were returned. All constructs were measured with existing scales. All items were measured on a seven-point Likert-type scale where 1=strongly disagree and 7=strongly agree. Data was submitted to regression, correlation reliability and factor analyses using SPSS 22.0. The average participant age was between 30 and 40 years old, and 44% of participants had more than five years of professional experience. 78% of them were men and 32% were women. The four components of emotional intelligence utilized to evaluate emotional intelligence were self-awareness, self-management, self-motivation, and social competence. Job performance served as the dependent variable. From the analysis Self-management, Self-motivation and social skill had ‘t’ values of 2.270, 0.175 and 2.283 respectively with the significant p value of 0.025, 0.21, and 0.025 respectively. This evidently indicates that emotional intelligence factors affect an employees’ motivation to perform.